PROGRAM ASIMILASI DAN BEBAS BERSYARAT DI LAPAS ANAK KELAS 1A KUPANG - Samara, Finsensius; Alfira Nata , Maria; Kurniawan Geong , Mario Pietro (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
This study examines the implementation of the assimilation and conditional release programs for Child Correctional Students (ANDIKPAS) at the Class IA Children’s Correctional Facility in Kupang. The research aims to identify the number of ANDIKPAS eligible for the programs, the requirements to participate, the program’s implementation timeline, challenges faced, and the number of participants in 2023. Findings show that 38 ANDIKPAS meet the requirements, with 18 successfully participating in the program in 2023. The primary requirements include serving half of their sentence, maintaining good behavior, and being free of serious disciplinary violations. Challenges identified include delays in the administrative process, limited facilities for rehabilitation, and societal stigma upon release. The study suggests improving coordination between institutions, enhancing rehabilitation facilities, reducing societal stigma, and involving family support to ensure the success of reintegration. Ongoing evaluation of the program is recommended for continued effectiveness.